2011
DOI: 10.1002/cjoc.201100005
|View full text |Cite
|
Sign up to set email alerts
|

A Green and Highly Efficient Protocol for Catalyst‐free Knoevenagel Condensation and Michael Addition of Aromatic Aldehydes with 1,3‐Cyclic Diketones in PEG‐400

Abstract: A convenient, highly efficient and green approach for synthesis of tetraketones from aromatic aldehydes with dimedone and 1,3-indanedione at room temperature in PEG-400 is described. The use of PEG-400 as the reaction medium and avoiding the use of any catalyst makes the process environmentally benign. Seven new compounds are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…(±)-Proline generates an electrophilic iminium ion from 4-nitrobenzaldehyde that readily reacts with 1 equiv of dimedone, forming a Knoevenagel adduct (Scheme ). Similar organocatalysis was exploited using β-alanine during the undergraduate Verley–Doebner preparation of cinnamic acids. , A subsequent Michael addition of the second dimedone equivalent furnished the isolated compound as a dienol rather than a tetraketone . Introductory-level undergraduate students confirmed this observation in their reports after acquiring product 1 H NMR and IR spectra.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…(±)-Proline generates an electrophilic iminium ion from 4-nitrobenzaldehyde that readily reacts with 1 equiv of dimedone, forming a Knoevenagel adduct (Scheme ). Similar organocatalysis was exploited using β-alanine during the undergraduate Verley–Doebner preparation of cinnamic acids. , A subsequent Michael addition of the second dimedone equivalent furnished the isolated compound as a dienol rather than a tetraketone . Introductory-level undergraduate students confirmed this observation in their reports after acquiring product 1 H NMR and IR spectra.…”
Section: Discussionmentioning
confidence: 86%
“…After reaction completion was determined by thin-layer chromatography, ice-cold water was added and stirring continued for 10 min, causing a white precipitate to form. The crude product was collected by vacuum filtration and recrystallized from absolute ethanol to generate purified 1 in typical yields of 30–80% (average student yield 55%, lit . yield 97%), mp 188–190 °C (lit .…”
Section: Experimental Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…PEG-400 has been reported as a green and effective solvent in the synthesis of bisdimedone analogs at room temperature by Firouzeh and his co-workers [74]. This protocol offered various advantages such as avoidance of hazardous organic solvents and catalyst, moderate to high yields (59%-98%), wide substrate scope, and simple experimental operation (Scheme 9: Method 4).…”
Section: Synthesis Of Bisdimedones Using Catalyst-free Conditionsmentioning
confidence: 99%
“…Thus, many researchers tend to use multicomponent reaction strategy. It has been found that the three‐component condensation constitutes an especially attractive synthetic strategy for rapid efficient route because the products are formed in single step without isolation of any intermediate, thus reducing reaction time, energy, and material use . The Biginelli reaction is one of the most important examples of multicomponent reaction for the synthesis of dihydropyrimidinone due to its wide range of biological activities .…”
Section: Introductionmentioning
confidence: 99%